Nikhil out loud - Pancholy, Maulik, 1974- (Balzer + Bray, 2022)
A thirteen-year-old voice actor for the children's animated show "Raj Reddy in Outer Space," Nikhil Shah moves with his mother from Los Angeles to small-town Ohio so his mother can help care for Nikhil's sick grandfather, Nana. Though he must deal with family tensions between his mother and grandparents at home, Nikhil quickly becomes a celebrity among his peers and easily wins the lead role in the school play. When he casually mentions to a school reporter that he is gay, it causes an uproar in the community and parents protest his involvement in the production. In addition to the controversy, Nikhil realizes that his voice is changing and his time on "Raj Reddy" is coming to an end. Fortunately, Nikhil receives support from his friends who help him deal with his messy life and stand beside him to reject the homophobia.